Peranan Pendidikan Bahasa Inggris Bagi Perkembangan Ilmu Lainnya - Rahula Hananuraga (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2022)
English is increasingly being used in indonesian society. This happens as a consequence of people being impacted by technology and social networking sites. One of them is the wide acceptance of english-language films among general audiences. Although english is an important world language and the common language of every country around the world, we must understand it well if we want to enter the global arena. In addition to the actions of governments and certain groups in countries where english is taught or used as a second or third language, here are some reasons why people quickly learn to use the language, especially financial reasons. A systematic review of the literature approach is used to analyze, identify, and evaluate all data on the problem of investigation with a view to addressing the stated research objectives. The slr method is divided into three stages: preparation, implementation, and evaluation. It turns out that english has a close relationship with other fields of study. In addition, english is one of the world's dialects which is used all over the world, especially in indonesia, because it is used in educational institutions and commerce. English also plays a role in the progress of the globalization process to date